2022
DOI: 10.3390/molecules27238626
|View full text |Cite
|
Sign up to set email alerts
|

Marigold Metabolites: Diversity and Separation Methods of Calendula Genus Phytochemicals from 1891 to 2022

Abstract: Marigold (Calendula), an important asteraceous genus, has a history of many centuries of therapeutic use in traditional and officinal medicines all over the world. The scientific study of Calendula metabolites was initiated at the end of the 18th century and has been successfully performed for more than a century. The result is an investigation of five species (i.e., C. officinalis, C. arvensis, C. suffruticosa, C. stellata, and C. tripterocarpa) and the discovery of 656 metabolites (i.e., mono-, sesqui-, di-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 133 publications
0
12
0
Order By: Relevance
“…With a few exceptions, we found the same carotenoids as previously described. 14,21 We detected the open-chain lycopene (8), γ-carotene (7), δ-carotene (17), as well as their cis-and di-cis-isomers, which were previously isolated and identified by Kishimoto et al 21 Among the carotene hydrocarbons, we also found α-carotene (16) and β-carotene (1) in small amounts. Monohydroxy carotenoids are represented by β-cryptoxanthin (15) and rubixanthin (6) and their cis-isomer.…”
Section: ■ Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…With a few exceptions, we found the same carotenoids as previously described. 14,21 We detected the open-chain lycopene (8), γ-carotene (7), δ-carotene (17), as well as their cis-and di-cis-isomers, which were previously isolated and identified by Kishimoto et al 21 Among the carotene hydrocarbons, we also found α-carotene (16) and β-carotene (1) in small amounts. Monohydroxy carotenoids are represented by β-cryptoxanthin (15) and rubixanthin (6) and their cis-isomer.…”
Section: ■ Discussionmentioning
confidence: 54%
“…The most important hydrophilic active ingredients of marigold are flavonoids (isorhamnetin, quercetin and quercetin glucosides, narcissin, calendoflavoids). , Lipophilic biomolecules of particular value to the cosmetic industry are the anti-inflammatory, antioxidant, and skin-regenerating carotenoids (β-carotene ( 1 ), (all- E )-lutein ( 2 ), (9 Z )-lutein, luteoxanthin ( 3 ), flavoxanthin ( 4 ), violaxanthin ( 5 ), rubixanthin ( 6 ), γ-carotene ( 7 ), and lycopene ( 8 ), Figure S1). In addition, the determination of Calendula genus metabolic products has a tradition of more than a century, during which 656 characteristic molecules have been identified for taxa …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic properties of C. officinalis are attributed to the presence of biologically active compounds. Among these, phenolic compounds and triterpenoids are the most abundant [ 5 ].…”
Section: Introductionmentioning
confidence: 99%